Centrality of the role of religion in the society - Laluddin, Hayatullah (LexisNexis, 2010)
Religion plays a central role in human life and civilisation. It is an independent force underlying the existence of society. This position invalidates the view of it being a mere dependent phenomenon of the historical forces, as held by some modern philosophers and social scientist. The centrality of religion in the society is clear from consideration of human being as a ‘religious being in essence’ and that of religion as a cosmic phenomenon governing man’s thought and civilisation. 1 In view of the significance of religion in the society, this article attempts to establish its centrality in the society by analysing its significance, nature and the root cause of the controversy between religion and science. It also delineates some questions of metaphysical nature and highlights the inadequacy of mere reliance on senses and pure reason in the context hence, the need for divine guidance. The spiritual aspect of life and its constructive role in social phenomenon is also dealt with in this article.